TIME-SERIES ANALYSIS OF LARGE IGNEOUS PROVINCES: 3500 MA TO PRESENT - Prokoph A.; Ernst R.E.; Buchan K.L. (My University, 2004)
We outline an efficient integrated wavelet, a spectral, and a cross-spectral approach for the time-series analysis of geologic data. Here these techniques are applied to a database of 154 large igneous provinces (LIPs) in order to test for cycles, trends, and abrupt changes in temporal distribution since 3500 Ma. The average frequency of events is relatively constant and supports an overall model of semicontinuous temporal emplacement of LIPs. However, several weak cycles were obtained in the analysis. Those of longest duration are a ∼170-m.yr. cycle from 1600 Ma to present and in the late Archean, a ∼330-m.yr. cycle from about 3000 to 1000 Ma, a cycle decreasing in length from 730 to 550 m.yr. over the interval 3500 Ma to present, and a still weaker cycle increasing from 900 to 1000 m.yr. over the interval 2000 Ma to present. Additional cycles of shorter duration include a ∼250-m.yr. cycle in the late Archean, a ∼230-m.yr. cycle in the Phanerozoic, a ∼105-m.yr. cycle in the early Proterozoic, and several !60-m.yr. cycles occurring in scattered intervals. The uncertainties in the cycle patterns preclude a simple correlation with previously interpreted forcing functions: a ∼30-m.yr. cometary impact, a 270-m.yr. galactic year, a 500–300-m.yr. supercontinent cycle, and a ∼800-m.yr. resonance between tidal and free oscillations of the core. However, our ∼170-m.yr. interval spacing is associated with clusters of LIP events over the past 1500 Ma. Future time-series analyses on improved versions of the LIP database (and appropriate subsets) will be required to test the robustness of the cycles we observe and to identify underlying forcing functions.